Contraceptive Utilization and Unmet Need for Contraception Among Women Undergoing Treatment for Tuberculosis in Addis Ababa, Ethiopia: a Cross-Sectional Study - Solomon S; Yitayew B; Kebede A (Dove Medical Press, 2022)
Semaria Solomon,1,* Berhanu Yitayew,2,* Abebaw Kebede3 1Department of Microbiology, Immunology and Parasitology, St. Paul's Hospital Millennium Medical College (SPHMMC), Addis Ababa, Ethiopia; 2College of Health Science, Debre Berhan University (DBU), Debre Berhan, Ethiopia; 3TB/HIV Research Directorate, Ethiopian Public Health Institute (EPHI), Addis Ababa, Ethiopia*These authors contributed equally to this workCorrespondence: Semaria Solomon, P.O.Box: 25181/1000, Addis Ababa, Ethiopia, Email semariasol@gmail.comIntroduction: Pregnancy can pose a risk to women on tuberculosis (TB) treatment with a threat to the wellbeing of the mother and fetus. Physiological and stress-related effects result when pregnancy occurs during TB illness and while on treatment. Hence, this study aimed to assess contraceptive utilization, unmet need among women on TB treatment, and integration of family planning (FP) services with TB clinics in Addis Ababa, Ethiopia.Methods: A facility-based cross-sectional study was conducted using an interviewer-administered questionnaire. A total of 316 women aged 18- 49 who were on TB treatment were enrolled. Contraceptive utilization rate, unmet need, and integration of FP and TB services were determined. Logistic regression models were conducted to identify factors associated with contraceptive utilization.Results: Among women on TB treatment 49 (41.9%) were using contraceptives. Out of contraceptive users, 10 (34.5%) used contraceptives to limit and 18 (62.1%) used to space. Only parity had a significant association with contraceptive utilization. Women who had 1- 3 children were less likely to use contraception than those who had ≥ 4 children. Among women who were married or sexually active, 12 (18.9%) had an unmet need. Of the study participants, 144 (45.6%) had been informed about FP services at the TB clinics.Conclusion: The contraceptive utilization rate in the current study (41.9%) is slightly higher than the national prevalence (36.2%) yet it is still low. Furthermore, the unmet need (18.9%) was lower than the national report for the general population (22%). Educating women about the risk of getting pregnant while visiting the health facility for TB medication will help to improve their chances of better recovery and avoid medication side effects on the fetus. TB guidelines can consider providing FP counseling when initiating treatment to provide women with the power of information to make deliberate decisions.Keywords: TB, contraceptive, unmet need